Pendampingan Budidaya Kopi Melalui Pelatihan Petik Merah dan Teknik Panen dalam Meningkatkan Kualitas Produksi di Desa Jengglungaharjo Kecamatan Tanggunggunung Kabupaten Tulungagung - Lestari, Mufida Diah; Suryaningrum, Dwi Ari; Alfattama, Lona Chinsia; Lestari, Wahyu Dwi; Nuryananda, Praja Firdaus; Tjahjono, Jojok Dwirido (Kadiri University, 2025)
This mentoring program on coffee cultivation, implemented through training in red-cherry picking and selective harvesting techniques, was conducted to improve the quality of coffee yields in Jengglungharjo Village, Tanggunggunung District, Tulungagung Regency. The abundant coffee production in the area holds significant potential as a driver of the local economy. However, the quality of the coffee beans has remained low due to mixed-harvest practices and the farmers’ limited understanding of proper harvesting procedures. The program was carried out in three main stages: delivering material on the importance of harvesting fully ripe coffee cherries, providing training on effective harvesting techniques, and offering initial post-harvest assistance to ensure that red-cherry yields were processed correctly. The results showed a significant improvement in farmers’ knowledge and skills in identifying ripe cherries and applying selective harvesting practices. Farmers began to understand the relationship between proper harvesting methods and improvements in coffee bean quality, including the increased proportion of premium-grade beans in both natural and full-washed processes. This training is expected to serve as an initial foundation for promoting more sustainable, productive, and economically valuable coffee cultivation practices for the community of Jengglungharjo Village. Program pendampingan budidaya kopi melalui pelatihan petik merah dan teknik panen selektif ini dilaksanakan untuk meningkatkan mutu hasil panen kopi di Desa Jengglungharjo, Kecamatan Tanggunggunung, Kabupaten Tulungagung. Produksi kopi yang melimpah di wilayah tersebut memiliki potensi besar sebagai penggerak ekonomi lokal. Namun, mutu biji kopi yang dihasilkan masih rendah akibat kebiasaan panen campur serta minimnya pemahaman petani mengenai prosedur panen yang tepat. Kegiatan ini dilaksanakan melalui tiga tahapan utama, yaitu penyampaian materi terkait pentingnya memanen buah kopi yang benar-benar matang, pelatihan teknik panen yang efektif, serta pendampingan pascapanen awal untuk memastikan hasil petik merah diproses secara benar. Hasil kegiatan menunjukkan peningkatan signifikan pada pengetahuan dan keterampilan petani dalam mengidentifikasi buah matang dan menerapkan panen selektif. Petani mulai memahami hubungan antara metode panen yang tepat dengan peningkatan kualitas biji kopi, termasuk meningkatnya proporsi biji berkualitas premium pada proses natural maupun full washed. Pelatihan ini diharapkan menjadi landasan awal untuk mewujudkan praktik budidaya kopi yang lebih berkelanjutan, produktif, dan bernilai ekonomi tinggi bagi masyarakat Desa Jengglungharjo